2007
DOI: 10.3171/jns-07/10/0784
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of meningioma consistency using fractional anisotropy value measured by magnetic resonance imaging

Abstract: The FA value calculated from preoperative MR DT imaging predicts meningioma consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 18 publications
0
45
1
2
Order By: Relevance
“…We expect that μFA may not only contribute to the investigation of complex WM geometries, but also in detecting microscopic anisotropy in tissues that are approximately isotropic on the voxel scale, for example, in GM (McNab et al, 2013; Truong et al, 2014). Further, the μFA and OP may provide complementing information to the FA and tensor shape analysis previously used in the differentiation of classic and atypical meningioma (Toh et al, 2008), detection of fibroblastic meningioma (Tropine et al, 2007), and in the preoperative estimation of tumor consistency (Kashimura et al, 2007), by removing the confounding effects of orientation dispersion which are otherwise ignored.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that μFA may not only contribute to the investigation of complex WM geometries, but also in detecting microscopic anisotropy in tissues that are approximately isotropic on the voxel scale, for example, in GM (McNab et al, 2013; Truong et al, 2014). Further, the μFA and OP may provide complementing information to the FA and tensor shape analysis previously used in the differentiation of classic and atypical meningioma (Toh et al, 2008), detection of fibroblastic meningioma (Tropine et al, 2007), and in the preoperative estimation of tumor consistency (Kashimura et al, 2007), by removing the confounding effects of orientation dispersion which are otherwise ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The method presented here is applicable to a wide variety of inquiries as it requires few assumptions about the investigated tissue and is implemented as a straight-forward modification to the conventional diffusion encoding sequence (Lasič et al, 2014; Szczepankiewicz et al, 2015). This is especially true if diffusion anisotropy parameters are intended to differentiate tumor subtypes (Jolapara et al, 2010; Sanverdi et al, 2012; Wang et al, 2012), preoperative estimation of tumor consistency (Kashimura et al, 2007; Tropine et al, 2007), delineation for biopsies (Kinoshita et al, 2008), and tumor proliferation (Beppu et al, 2005). Such cases warrant the use of MK A or μFA, since conventional measures of anisotropy ignore the interaction between orientation coherence and voxel size, and may therefore be strongly biased (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the μFA stratified the fibroblastic meningiomas from the other subtypes, i.e., the fibroblastic tumors had the four highest μFA values, whereas the same stratification was not observed for FA. It may therefore be possible to use μFA for pre-surgical toughness estimation in meningiomas (Kashimura et al, 2007; Tropine et al, 2007). We emphasize that the tissue with the highest μFA is not necessarily mapped to the highest FA due to variable orientation coherence (black arrows point to the same tumor sample).…”
Section: Figurementioning
confidence: 99%
“…However, the authors did feel that soft tumors tended to show hyperintensity on T2WI. Similarly, Kashimura et al found that there was no association between T2WI and consistency 25 . A more recent larger series from Romani et al also found no association using T1- or T2WI, as well as FLAIR or proton density weighted imaging (PDWI) 26 .…”
Section: Neuroimaging Studies Of Meningioma Consistencymentioning
confidence: 93%
“…However, these results were not compared with an actual assessment of meningioma consistency. The same year, Kashimura et al showed that FA values for hard meningiomas were significantly higher compared to soft ones 25 . Using an FA cut-off value of 0.3, they demonstrated sensitivity of 91% and specificity of 67%.…”
Section: Neuroimaging Studies Of Meningioma Consistencymentioning
confidence: 94%